Implikasi Keberadaan Hutan Negara terhadap Perkembangan Desa di Kecamatan Segah Kabupaten Berau Provinsi Kalimantan Timur - Sitti Hadijah; Ernan Rustiadi; Endriatmo Soetarto (TATALOKA, 2021)
The state forest existence is expected to provide maximum benefits for the people's prosperity. This study identified the forest state existence through a land tenure structure in Segah District Berau Regency East Kalimantan Province. It also described a portrait of rural development including the condition of infrastructure and community income/expenditure, and identified the influence of state forest existence on rural development. The methods used to analyze the structure of land tenure by overlaying land cover maps and boundaries of area functions in each village, then classifying villages using a matrix of plots based on the percentage of forest and forest area. Analysis of rural development was carried out using scalogram analysis and oneway ANOVA. Meanwhile, the analysis of the influence of state forest existence on rural development was carried out using descriptive analysis and multiple linear regression. The results of this study showed that the land cover of the forest and land tenure of forest area were dominant. This means that the land tenure structure in the administrative area of Segah District was dominated by state forest. Rural development in terms of infrastructure was found in a condition that was quite even lacking of the needs of the rural population, while average household expenditure is above the national average minimum expenditure limit. The state forest existence was indicated to have a role in influencing the development of rural infrastructure and household expenditure, especially in the activity of entering the forest which can reduce the expenditure of primary household needs.